Using primary care electronic health record data for comparative effectiveness research: experience of data quality assessment and preprocessing in The Netherlands. (July 2016) - Huang, Yunyu; Voorham, Jaco; Haaijer-Ruskamp, Flora M
Aim: Details of data quality and how quality issues were solved have not been reported in published comparative effectiveness studies using electronic health record data.Methods: We developed a conceptual framework of data quality assessment and preprocessing and apply it to a study comparing angiotensin-converting enzyme inhibitors with angiotensin receptor blockerss on renal function decline in diabetes patients.Results: The framework establishes a line of thought to identify and act on data issues. The core concept is to evaluate whether data are fit-for-use for research tasks. Possible quality problems are listed through specific signal detections, and verified whether they are true problems. Optimal solutions are selected for the identified problems.Conclusion: This framework can be used in observational studies to improve validity of results.